Luminescent properties of BaxMg(2−x)F4:W ceramics - Koketai, T; Strelkova, A.V.; Zhunusbekov, A.M.; Karipbayev, Zh.T.; Lisitsyna, L.A.; Chakin, A.M. (Eurasian Journal of Physics and Functional Materials, 2026)
Ceramics based on alkaline earth metal fluorides activated by tungsten has been obtained by radiation synthesis. The synthesis was realized by direct action on the mixture with an activator of a powerful flow of high-energy electrons without the use of any additives to facilitate the synthesis. It has been established that the resulting ceramics have luminescent properties characteristic of tungsten-activated materials based on metal fluorides. Recommended Citation Koketai, T.A.; Strelkova, A.V.; Zhunusbekov, A.M.; Karipbayev, Zh.T.; Lisitsyna, L.A.; and Chakin, A.M. (2023) "Luminescent properties of BaxMg(2−x)F4:W ceramics," Eurasian Journal of Physics and Functional Materials: Vol. 7: No. 1, Article 2. DOI: https://doi.org/10.32523/ejpfm.2023070103